War and violence in ancient Greece - Wees, Hans van; Beston, Paul (The Classical Press of Wales, 2009)
The study of Greek warfare should involve much more than reconstructing the experience of combat or revisiting the great wars of the classical period. Here, a distinguished cast of international scholars explores beyond the usual thematic and chronological boundaries. Ranging from the heroes of Homer to the kings and cities of the hellenistic age, the contributors set war in the context of other forms of Greek violence, private and public. At every turn they challenge received ideas about the causes and conduct of war, its development and its place in Greek society and culture.